MANAJEMEN PENGEMBANGAN MUTU DOSEN UPI : Studi Kasus Manajemen Pengembangan Mutu Dosen UPI Bandung dan Upi Jakarta - Sanusi, - (1995)
As one of the agent of socialization, the function of IKIP is to transfer and to transform the culture from one generation to another generation. The more special function is to prepare the teachers for the primary and secondary schools. The low quality of its outputs is one of the problems confronted by IKIPs, term of the average academic achievement, the irrelevancy of the outputs to the market need (in term of instrumental dimension), and in term of attitude, personalities and the intellectual qualities (intrinsic dimension).There are many factors related those problems, such as curriculum (as representation of making faculties, departments or programs), supporting facilities (operational and staffing funds), and human resources (administrations staffs, lecturers and students). But the most important factors are lecturers and students as the central variables of educational system. Based on these problems, the most important effort in eliminating the weaknesses is by increasing the quality of the lecturers that will give the effect to the improvement of the student's qualities. This study is focused on the succes determining factors in developing the quality of the lecturer. Through qualitative approach, the result are as follows.Three main factors that support each other in developing lecturer quality, are educational management, organizational strategy and the state of the personal. Educational management consist of policy making, programming, technical and the form and limitation of the duty of institution.